BET 1: In paracetamol overdose, is oral N-acetylcysteine as effective as intravenous N-acetylcysteine?. Issue 10 (24th September 2018) - Woodhead, Kathryn; Foex, Bernard A
Abstract : A short-cut review was carried out to establish whether oral N-acetylcysteine is as effective as intravenous N-acetylcysteine in the management of paracetamol overdose. Seven studies were directly relevant to the question. The author, year and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that oral N-acetylcysteine is a safe alternative in patients for whom the intravenous route is not an option.